The Limits and Challenges of Comparativism - Esin Örücü; Esra Seçkin (İstanbul Hukuk Mecmuası)
This paper examines the limits of comparativism under two categories; those limits related to the comparatist herself -the intrinsic, and those related to other factors such as the context, the environment and the purpose, the limits of its use; the limits of its methodology; the limits of topics to be compared and so on -the extrinsic. These limits are not rigid and at times may overlap. Beyond these, the paper also delves into further challenges. As a final note, the paper reminds the reader that although comparative law is not a panacea to all our woes, the comparative lawyer will remain an essential actor in our ceuntry. She must endevaour to surpass the limitations enslaving both her, the intrinsic challenges, and her subjects, the extrinsic challenges.